Potential Therapeutic Strategies for Hypertension-Exacerbated Cardiotoxicity of Anticancer Drugs - Kuriakose, Robin K. (Oxid Med Cell Longev, 2016)
Despite their recognized cardiotoxic effects, anthracyclines remain an essential component in many anticancer regimens due to their superior antitumor efficacy. Epidemiologic data revealed that about one-third of cancer patients have hypertension, which is the most common comorbidity in cancer registries. The purpose of this review is to assess whether anthracycline chemotherapy exacerbates cardiotoxicity in patients with hypertension. A link between hypertension comorbidity and anthracycline-induced cardiotoxicity (AIC) was first suggested in 1979. Subsequent preclinical and clinical studies have supported the notion that hypertension is a major risk factor for AIC, along with the cumulative anthracycline dosage. There are several common or overlapping pathological mechanisms in AIC and hypertension, such as oxidative stress. Current evidence supports the utility of cardioprotective modalities as adjunct treatment prior to and during anthracycline chemotherapy. Several promising cardioprotective approaches against AIC pathologies include dexrazoxane, early hypertension management, and dietary supplementation of nitrate with beetroot juice or other medicinal botanical derivatives (e.g., visnagin and Danshen), which have both antihypertensive and anti-AIC properties. Future research is warranted to further elucidate the mechanisms of hypertension and AIC comorbidity and to conduct well-controlled clinical trials for identifying effective clinical strategies to improve long-term prognoses in this subgroup of cancer patients.